PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN KEPERCAYAAN SEBAGAI MODERASI TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN DI UD.SUMBER TANI - Dhiyaurohman, Alfandi Wavin; Henryanto, Aria Gana; Kenang, Irantha Hendrika (PERFORMA, 2022)
The development of the agricultural business sector is currently experiencing a fairly positive increase. According to data from the Central Statistics Agency (BPS) provides information that agriculture is the highest contributor to national economic growth. Seeing good opportunities for agricultural business actors such as UD.Sumber Tani. The object used in this research is UD.Sumber Tani which was founded in 2003 in Ponorogo, East Java. This study aims to analyze the effect of product quality, service quality, and trust as a moderator on customer satisfaction and customer loyalty at UD.Sumber Tani. This study uses a quantitative approach. The population in this study are UD Sumber Tani customers. The sample used in the study was 60 respondents. The data was collected using a questionnaire method which was filled out using a Likert Scale with the Partial Least Square (PLS) analysis method and the SmartPLS 3.0 tool. The results of this study indicate that product quality has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction, trust does not moderate the relationship between customer satisfaction and loyalty, customer satisfaction has a significant effect on customer loyalty at UD.Sumber Tani.